The Clinical Efficacy and Safety of Flexible Ureteroscopic Treatment for Parapelvic Renal Cyst and Secondary Renal Stone - Wen, Jiaming; Xu, Gang; He, Gaofei; Wang, Bohan; Mao, XiaWa; Zhang, Shigeng (Urology Journal, 2020)
Purpose: To explore the efficacy and safety of flexible ureteroscopic incision and drainage and flexible ureteroscopic lithotripsy for treatment of parapelvic renal cyst combined with secondary renal stone. Materials and Methods: 28 patients with parapelvic renal cyst combined with renal stone were treated with flexible ureteroscopic incision and drainage and flexible ureteroscopic lithotripsy simultaneously from May 2010 to December 2016. The follow-up was made 1, 3, 6?12 months and 2 years after surgical treatment in our outpatient department. Ultrasonic examination and CT were used to detect the residual stone and recurrence of renal cyst. Results: The mean age of the patients was 45.3 ± 18.6 years. The average size of the parapelvic renal cysts was 4.3 ± 1.6 cm, including 27 with Bosniak category I and 1 patient with Bosniak II renal cysts. The mean size of the renal stones was 14.3 ± 3.9 mm. The mean operative time was 53.4 ± 20.7 minutes and the mean blood loss was 10.8 ± 5.6 ml. The mean hospitalization time was 3.2 ± 0.7 days. No severe complications were encountered. The complications included transient fever ( > 38°C) in 3 patients and significant hemorrhage in 1 patient. The stone-free rates one month and three months after operation were 89.3% and 96.4%, respectively. During the 2 years follow-up, the cyst recurrence rate was 14.3% and the stone recurrence rate was 7.1%. Conclusion: In this study, we firstly demonstrated that it is safe and effective to treat both renal stone and parapelvic renal cyst simultaneously by flexible ureteroscopic lithotripsy and flexible ureteroscopic incision and drainage, with satisfactory stone free rate and low cyst recurrence rate.